Factors affecting the reproductive performance of zebu cattle on the Adamawa Plateau - Mbah, D.A.; Abassa, P.K.; Zamba, P.; Tawah, L.C.; Messine, O.; Oumate, H. (ECA, 1991)
The reproduction of Gudali and Wakwa cattle are investigated. Reproduction data on Gudali and Wakwa cattle on Adamawa Plateau from 1967 to 1988 were analysed. Age at first calving was not affected by breed, year of birth and season of calving (P>.05). Mean calving interval (536.9 ± 17.3 days) was affected.